Rancangan dan Simulasi Sistem Kendali pada Robot Make Up dengan Pendekatan Human-Robot Interaction - Rivina Kayla Nazeva; Tata Sutabri (Router : Jurnal Teknik Informatika dan Terapan, 2024)
This research focuses on designing and simulating a makeup robot control system with a Human-Robot Interaction (HRI) approach. The main goal is to develop a robot that is not only efficient in applying makeup, but also able to interact directly with users. The design of this robot is designed with attention to anthropomorphism and non-verbal interaction, in order to improve user comfort and experience during the use process. This control system leverages cutting-edge sensor technology, such as facial recognition and expression analysis, to detect user emotions and adjust the robot's response in real-time. The simulation process is carried out using the Robot Operating System (ROS) to develop an algorithm that supports task coordination between robots and humans as well as interactive feedback. The results of the simulation show that the robot is able to recognize the user's emotions and adjust their actions, thus creating a more intuitive and responsive interaction experience. This research has made a significant contribution to the development of robotics technology in the field of beauty, thereby improving the user experience in personal care. The findings also pave the way for further research into more complex human-robot interactions that are responsive to individual needs.